SUSTAINABILITY OF SOCIAL ENTREPRENEURSHIP: A PHENOMENOLOGICAL STUDY OF THE BALANCE BETWEEN SOCIAL MISSION AND FINANCIAL GOALS - Qonita Rey; Bunga Aditi; Iman Indrafana KH; Muhammad Rido; Muhammad Zacky Fuadi (Universitas Efarina, 2023)
This study aims to examineSustainability of Social Entrepreneurship: A Phenomenological Study of the Balance Between Social Mission and Financial Goals.The qualitative phenomenological research method allows researchers to deeply understand the subjective experiences of social entrepreneurs in managing the balance between social mission and financial goals. This approach provides rich and in-depth insights through thematic analysis and data triangulation. With a solid theoretical foundation, systematic research process, and thorough validation of findings, the results of this study are expected to be able to provide significant contributions to the study of social business sustainability. In some cases, social entrepreneurs prioritize profitability at the beginning of the business establishment to ensure the sustainability of the organization, and only then prioritize social impact after achieving financial stability. This flexible approach allows them to adapt to external changes, such as changing market conditions or community needs. Sustainability in social entrepreneurship depends heavily on the ability of actors to create a dynamic balance between social mission and financial goals. While social mission is often the top priority, healthy profitability is also important to support and enlarge the desired social impact. Success in achieving this balance requires not only innovative strategies, but also flexibility in adjusting priorities based on changes in the external environment. With the right approach, social entrepreneurship can be a successful model for creating positive social change while ensuring financial sustainability.